A historical perspective on fire research in East and Southern African grasslands and savannas. Issue 1 (2nd January 2022) - Pooley, Simon
Abstract : This paper provides a history of attempts to understand and manage fire in the grasslands and savannas of eastern and southern Africa from c. 1900 to 2010. Given the brevity of the paper and the author's expertise, there is a focus on science and management in South Africa, though wider networks of research and expertise across the region are discussed. There is a focus on a few key figures like Charles Swynnerton, John Phillips and Winston Trollope, with references provided for other important historical figures like John William Bews. The emphasis is on scientific research and expert-led thinking on fire and fire management in vegetation, with brief discussion of African approaches and the extent to which they have been ignored or have influenced scientific thinking. Fire in relation to invasive species is not covered.